Analisis Kinerja Instalasi Farmasi RS Medika Mulya Wonogiri pada Perspektif Pertumbuhan dan Pembelajaran dan Perspektif Proses Bisnis Internal - Samuel Budi; Achmad Fudholi; Satibi Satibi (Fakultas Farmasi Universitas Setia Budi, 2011)
Accompanying to higher demands and expectations of customers to healthy service, so that healthy servicing agent needs to improve a quality service. Balanced Scorecard is a power-full instrument to evaluate management, it can asses work quality of Hospital Pharmacy Department from four perspectives such as financial, customer, servicing process, and regularly learning and growth. This research included descriptively study case research. Qualitatively and quantitatively data were collected by retrospective and prospective methods. These were collected by: document observation, direct observation, and questionnaire distribution. Qualitatively data have been analyzed for contents, and quantitatively data have been analyzed statistically.Result of research showed that: 1) work qualities based on perspectives of learning and growth are: 44% and 82% IFARS employee who have job training in 2008 and 2009, respectively; productivity of employee is 84,65%; indicator of SIM development is 45% in 2009, percentage of work ethos scale is 78,54%. 2) work quality based on perspective of internal business process: 99,35% for medicines available in 2008; the average time that is needed to preparing non-blended and blended medicines is 7,63 minutes and 20,33 minutes, respectively; the average time that is needed to providing information is 42,25 seconds; in line level is 100%; and proportion for give medicines correctly is 100%.